For debate: problems with the DMF index pertinent to dental caries data analysis - Broadbent JM, Thomson WM (Blackwell Synergy, 2005)
The Decayed, Missing, Filled (DMF) index has been used for over 50 years and is well established as the key measure of caries experience in dental epidemiology.